2017
DOI: 10.1161/strokeaha.116.015131
|View full text |Cite
|
Sign up to set email alerts
|

Door-to-Imaging Time for Acute Stroke Patients Is Adversely Affected by Emergency Department Crowding

Abstract: Background and Purpose-National guidelines call for door-to-imaging time (DIT) within 25 minutes for suspected acute stroke patients. Studies examining factors that affect DIT have focused primarily on stroke-specific care processes and patient-specific factors. We hypothesized that emergency department (ED) crowding is associated with longer DIT. Methods-We conducted a retrospective investigation of 1 year of consecutive patients in our prospective Code Stroke registry, which included all ED stroke team activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 22 publications
0
55
1
Order By: Relevance
“…Effects on patients included delays in being assessed and receiving required care [ 29 , 30 , 76 79 , 81 , 83 , 84 , 87 , 90 , 91 , 93 , 94 , 97 , 98 , 103 , 104 ], increased frequency of exposure to error [ 18 ], including medication errors [ 17 ], reduced patient satisfaction [ 102 ], increased inpatient length of stay (IPLOS) [ 82 , 88 , 95 , 99 , 101 ] and poorer outcomes [ 29 , 30 , 75 , 92 , 107 ]; the latter included increased inpatient mortality [ 3 , 80 , 85 , 96 , 99 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Effects on patients included delays in being assessed and receiving required care [ 29 , 30 , 76 79 , 81 , 83 , 84 , 87 , 90 , 91 , 93 , 94 , 97 , 98 , 103 , 104 ], increased frequency of exposure to error [ 18 ], including medication errors [ 17 ], reduced patient satisfaction [ 102 ], increased inpatient length of stay (IPLOS) [ 82 , 88 , 95 , 99 , 101 ] and poorer outcomes [ 29 , 30 , 75 , 92 , 107 ]; the latter included increased inpatient mortality [ 3 , 80 , 85 , 96 , 99 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with acute cerebrovascular accidents, ED overcrowding is associated with delay to CT scanning, and boarding of these patients is associated with increased mortality, complications, and poorer recovery [26,27]. Overcrowding increases delays to antibiotics in patients with pneumonia as well as febrile neonates [28,29].…”
Section: The Impact Of Overcrowding On Patient Carementioning
confidence: 99%
“…A recent study at an academic medical center revealed that emergency room occupancy can adversely influence door-toimaging times in acute stroke patients. 24 With increasing awareness of acute stroke symptoms and available treatments, there is a growing volume of patients requiring triage in the ED. Directly admitting the LVO population to the neuroangiography suite partitions this group to a different portion of the hospital and allows for better utilization of ED resources.…”
Section: July 2017mentioning
confidence: 99%